(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article describes the state of regulation of artificial intelligence technologies development in the world and Ukraine, highlights the features of the use of AI, in particular large language models such as ChatGPT chatbot in the educational sector, including in higher education institutions, analyses a number of documents that contain recommendations for the use of artificial intelligence technologies in teaching, learning and research. The analysis has been carried out and the results of the research have been summarized by surveying students, lecturers and researchers of Borys Grinchenko Kyiv Metropolitan University regarding the problem and ways of using the digital technology of artificial intelligence chatbot ChatGPT when writing academic texts. The state of use of the specified technology in the educational and scientific activities of Borys Grinchenko Kyiv Metropolitan University has been determined, in particular, the number of respondents who are familiar with the chatbot and technologies that recognize its use in the text, and those who use them when writing academic texts, the frequency of such requests; the opinion of the interviewees has been recorded regarding the fair and ethical use of this technology and the need to indicate this fact in academic texts; the attitude of the survey participants to the need for state regulation of the use of ChatGPT in scientific and educational activities of higher education institutions, as well as normative regulation at Borys Grinchenko Kyiv Metropolitan University, has been clarified; the main risks and challenges of using this artificial intelligence technology in the educational and scientific activities of the higher education institution expressed by the respondents have been summarized; the need to hold events at Grinchenko University regarding familiarization with the digital technology of artificial intelligence of ChatGPT chatbot, the risks and challenges arising from its use in educational and research activities have been determined. A model of using artificial intelligence technologies, in particular ChatGPT chatbot in educational and scientific activities of Grinchenko University, has been proposed and relevant recommendations have been developed.